PENGARUH KOMPENSASI, JOB CRAFTING DAN JOB EMBEDDEDNESS TERHADAP TURNOVER INTENTION - Wahyu Muhammad Rizky; Desy Prastyani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to analyze the effect of compensation, job crafting, and job embeddeness on turnover intention. Compensation is important for retaining employees who can contribute to the company's sustainability. This type of research is quantitative through a purposive sampling technique with 220 respondents who are employees of Telecommunication companies in Jakarta. Primary data analysis was conducted using the Structural Equation Model Partial Least Square (SEM-PLS) method. The results of this study indicate that turnover intention can decrease if compensation is high and is influenced by job crafting and job embeddeness. In this study, there are three hypotheses that have a negative effect: compensation has a negative effect on turnover intention, job crafting has a negative effect on turnover intention, and job embeddedness has a negative effect on turnover intention. Thus, the findings of this study can be used to evaluate telecommunications companies.